A Contextual Project-Based Instructional Design Model Construction and Validation to Develop Students Creativity - Permata Nugrahani; Sunardi; Fatma Sukmawati (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Lack of mathematical creativity in the System of Linear Equations in Three Variables is a very important concern at SMA Pangudi Luhur St. Yosef Surakarta, mostly because of teaching by formula and the abstractness of the matter. The aim of the research was to design a Contextual Project-Based Learning (CoPjBL) approach to overcome the problems. This research employed a Research and Development (R&D) approach. Validity of the approach was checked by six experts, including two instructional designers, two subject matter experts in mathematics, and two education experts. Data analysis was done in a quantitative way by Aiken’s V index. It was developed to combine seven context pillars, including Constructivism, Inquiry, Questioning, Learning Community, Modeling, Reflection, and Authentic Assessment into its learning syntax. Results of validity testing proved to be very valid overall, showing an Aiken’s V of 0.92 (Very Valid). Detail scores of validity test showed 0.93 for design, 0.92 for subject matter, and 0.90 for education experts. This indicated a very high level of validity showing the CoPjBL approach to be very effective in offering a proper learning syntax to connect abstract math subjects to the real-world situation. Thus, the approach could be considered very suitable to be used to improve students' creative thinking abilities.